2000
DOI: 10.1080/001401300421752
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 3-D human foot forms using the Free Form Deformation method and its application in grading shoe lasts

Abstract: An effective way to design well-fitting products is to analyse human body forms and to classify them into several groups. In the present study, a new method is proposed to analyse human body forms using the FFD (Free Form Deformation) technique. The FFD method is a way to deform the shapes of object smoothly by moving control lattice points set around the object. The reference body form is automatically deformed to coincide with the other body forms using the FFD method. The dissimilarity is defined by the mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(62 citation statements)
references
References 7 publications
0
59
0
3
Order By: Relevance
“…Traditionally, the most frequently used measures for the determination of sizes were foot length and ball girth. However, different studies [4] have demonstrated that the increase in foot length and ball girth is not proportional. Furthermore, girth measures (ball, waist and instep) are largely correlated to each other and to other measures, except for foot length.…”
Section: Foot Features and Last Dimensionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Traditionally, the most frequently used measures for the determination of sizes were foot length and ball girth. However, different studies [4] have demonstrated that the increase in foot length and ball girth is not proportional. Furthermore, girth measures (ball, waist and instep) are largely correlated to each other and to other measures, except for foot length.…”
Section: Foot Features and Last Dimensionsmentioning
confidence: 99%
“…This approach did not describe in detail the equations employed to grade the last, but highlighted that the grading is performed proportionally. As mentioned above, several studies concluded that there is little correlation between length increase and ball girth increase [4], therefore, it would be necessary to analyse the results of the proposed method to check the adaptation of the resulting last to the user's foot.…”
Section: Shoe Last Grading Techniquesmentioning
confidence: 99%
See 3 more Smart Citations